How Negative Is Negative Information - Simoes, Elisabeth; Sokolov, Alexander N.; Hahn, Markus; Fallgatter, Andreas J.; Brucker, Sara Y.; Wallwiener, Diethelm; Pavlova, Marina A. (Frontiers in Neuroscience, 2021)
Daily, we face a plenty of negative information that can profoundly affect our perception and behaviour. During devastating events such as the current COVID 19 pandemic, negative messages may hinder reasoning at individual level and social decisions in the society at large. These effects vary across genders in neurotypical populations (being more evident in women) and may be even more pronounced in individuals with neuropsychiatric disorders such as depression. Here, we examine if negative information impacts reasoning on a perceptual task in females with breast cancer, a life-threatening disease. Two groups of patients and two groups of matched controls (NTOTAL= 80; median age, 50 years) accomplished a psychometrically standardized social cognition and reasoning task receiving either the standard instruction solely or additional negative information. Performance substantially dropped in patients and matched controls who received negative information compared to those who did not. Moreover, patients with negative information scored much lower not only compared with controls but also with patients without negative information. We suggest the effects of negative information are mediated by distributed brain networks involved in affective processing and emotional memory. The findings offer novel insights on impact of negative information on social perception and decision making during life-threatening events, fostering better understanding of its neurobiological underpinnings.